Surfactant Enhanced Bioremediation of Hydrocarbon Contaminated Soils Using Alkyl Polyglucoside - Ezekiel, C.E.; Osuji, Leo C.; Onojake, M. C. (Sciencedomain International, 2021)
Bioremediation is an efficient and environmentally friendly method for the degradation of petroleum hydrocarbons in contaminated soils. This study investigated the effects of biosurfactant alkyl polyglycosides (APG) on enhanced biodegradation of petroleum hydrocarbon contaminated soils. Three soil samples were contaminated with two different grades of crude oil (medium and Light). Alkyl polyglucoside was synthesised and subjected to FTIR for comfirmation of the product before it was applied in the remediation of contaminated soil. The alkyl polyglucoside is used as a treatment regime in the remediation of the hydrocarbon contamination in the three soil samples. Results of total petroleum hydrocarbons (TPH) before remediation with bio-surfactant showed that samples contaminated with medium crude for Eneka, Ozuoba and Rukpokwu were 15744.00 mg/kg, 11359.00 mg/kg and 11470.00 mg/kg respectively and after remediation reduced to 4276.00 mg/kg, 4265.00 mg/kg, and 3205.00 mg/kg, showing a reduction percentage of 72.84%, 62.44% and 72.05% respectively. Soil samples contaminated with light crude showed result of TPH of 11339.00 mg/kg, 10662 mg/kg and 10226 mg/kg and after remediation reduced to 2981 mg/kg, 3879 mg/kg, and 4245 mg/kg respectively showing a reduction percentage of 73.71%, 63.62 % and 58.49% respectively. The enhanced efficiency of the bio-surfactant at degrading total petroleum hydrocarbons was achieved as a result of the increased solubility thus improving the bioavailability of the hydrocarbons due to the action of the alkyl polyglucoside.
Asian Journal of Physical and Chemical Sciences, Volume 9, Issue 3, Page 17-28
Keywords: Bioremediation; petroleum hydrocarbon; contaminated soil; bio-surfactant; alkyl polyglucoside; bioavailaibility; STEM; University of Port Harcourt